Rapid green synthesis of silver and gold nanoparticles using Dendropanax morbifera leaf extract and their anticancer activities - Wang, Chao (Int J Nanomedicine, 2016)
Dendropanax morbifera Léveille is an oriental medicinal plant that is traditionally used in folk medicine and grows in a specific region of South Korea. We aimed to enhance the utilization of D. morbifera medicinal plants for synthesis of silver nanoparticles (AgNPs) and gold nanoparticles (AuNPs). D. morbifera leaf extract acted as both a reducing and a stabilizing agent that rapidly synthesized Dendropanax AgNPs (D-AgNPs) and Dendropanax AuNPs (D-AuNPs). The D-AgNPs and D-AuNPs were characterized by ultraviolet-visible spectroscopy, energy dispersive X-ray analysis, elemental mapping, field emission transmission electron microscopy, X-ray diffraction, and dynamic light scattering. The characterizations revealed that the D-AgNPs and D-AuNPs were in polygon and hexagon shapes with average sizes of 100–150 nm and 10–20 nm, respectively. The important outcomes were the synthesis of AgNPs and AuNPs within 1 hour and 3 minutes, respectively, avoiding the subsequent processing for removal of any toxic components or for stabilizing the nanoparticles. Additionally, D-AgNPs and D-AuNPs were examined for cytotoxicity in a human keratinocyte cell line and in A549 human lung cancer cell line. The results indicated that D-AgNPs exhibited less cytotoxicity in the human keratinocyte cell line at 100 µg/mL after 48 hours. On the other hand, D-AgNPs showed potent cytotoxicity in the lung cancer cells at the same concentration after 48 hours, whereas D-AuNPs did not exhibit cytotoxicity in both cell lines at the same concentration. However, both D-AgNPs and D-AuNPs at 50 µg/mL enhanced the cytotoxicity of ginsenoside compound K at 25 µM after 48 hours of treatment compared with CK alone. We believe that this rapid green synthesis of D-AgNPs and D-AuNPs is a valuable addition to the applications of D. morbifera medicinal plant. D-AuNPs can be used as carriers for drug delivery and in cancer therapy due to their lack of normal cell cytotoxicity.